2017
DOI: 10.1016/j.cgh.2016.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prevalence of Crohn’s Disease and Ulcerative Colitis in Olmsted County, Minnesota From 1970 Through 2010

Abstract: Background & Aims The incidence and prevalence of inflammatory bowel diseases (IBD) continue to increase worldwide. We sought to update incidence rates of Crohn's disease (CD) and ulcerative colitis (UC) in a well-defined United States (US) population, calculating values for Olmsted County, Minnesota through 2010. We also calculated prevalence values. Methods The resources of the Rochester Epidemiology Project were used to identify county residents who were diagnosed with IBD (CD or UC), based on previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
211
4
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 368 publications
(233 citation statements)
references
References 28 publications
5
211
4
13
Order By: Relevance
“…These cases have been previously validated. 36, 37 Exclusion criteria included HIV infection, any solid organ or bone marrow transplant, current malignancy or chemotherapy during the study period, hereditary immunocompromising conditions, or history of splenectomy.…”
Section: Methodsmentioning
confidence: 99%
“…These cases have been previously validated. 36, 37 Exclusion criteria included HIV infection, any solid organ or bone marrow transplant, current malignancy or chemotherapy during the study period, hereditary immunocompromising conditions, or history of splenectomy.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies originate from Europe and North America, where the highest incidence rates have been reported. In Olmsted County, Minnesota, USA, the incidence of CD increased from 8.7 to 10.7 per 100,000 person‐years between 1970 and 2000; the incidence of UC increased from 10.7 to 12.2 per 100,000 between 2000 and 2010 . In Canada, the reported incidence rates vary considerably across regions.…”
Section: Introductionmentioning
confidence: 99%
“…Given the chronic nature, early onset and relatively low mortality associated with IBD, the prevalence of IBD increases significantly over time in accordance with an aging population and the global increase in disease incidence. Population‐based studies in Olmsted County showed that the prevalence of CD has increased from 213.9 to 246.7 per 100,000 person‐years from 2001 to 2011 . Recent data from Canada reported a prevalence of IBD at 725 per 100,000 and is steadily increasing with an AAPC of +2.86% .…”
Section: Introductionmentioning
confidence: 99%
“…1 IBD is characterized by relapsing and remitting episodes of mucosal inflammation. We have therapeutics aimed at dampening the immune dysregulation such as anti-TNF-α antibodies that have demonstrated efficacy 24 , but they are often complicated by significant adverse effects and cost considerations.…”
Section: Introductionmentioning
confidence: 99%